The GLP-1 Receptor Agonist Exenatide Ameliorates Bone Composition and Tissue Material Properties in High Fat Fed Diabetic Mice - Mansur, Sity Aishah; Mieczkowska, Aleksandra; Flatt, Peter R.; Chappard, Daniel; Irwin, Nigel; Mabilleau, Guillaume (Frontiers in Endocrinology, 2019)
Type 2 diabetes mellitus (T2DM) has recently been recognized as a significant risk factor for bone fragility. Careful investigations of bone mechanical properties in human studies suggested possible alterations of bone composition, although this axis has poorly been investigated. The main aim of this study was to evaluate the impact of high fat diet-induced diabetes and therapy using the clinically approved GLP-1 receptor agonist, exenatide, on tissue bone mechanical properties and compositional parameters. Male mice had free access to high fat diet for 16 weeks to induce diabetes prior to commencement of the study. Exenatide was administered twice daily by i.p. injection at a dose of 25 nmol/kg for 52 days. Normal and high fat diet fed (HFD) mice injected with saline were used as controls. Bone mechanical properties was assessed at the organ level by 3-point bending and at the tissue level by nanoindentation. Bone microarchitecture was investigated by microcomputed tomography and bone composition was evaluated by Fourier transform infrared imaging. HFD mice exhibited profound alterations of bone mechanical properties at both the organ and tissue level. Collagen maturity as well as trabecular and cortical bone microarchitectures were abnormal. Administration of exenatide, led to clear ameliorations in bone mechanical properties at the organ and tissue levels by modifications of both cortical microarchitecture and bone compositional parameters (collagen maturity, mineral crystallinity, carbonate/phosphate ratio, acid phosphate content). These results bring new light on the mode of action of exenatide in bone physiology and demonstrate the value of GLP-1 mimetics in the treatment of fragility fractures in diabetes.